Effect of Bank Indonesia Rate on Total Financing of The Islamic Banks for The 2014-2020 Period with Third-Party Funds as a Moderating Variable - Ridlwan, Ahmad Ajib; Kumala, Firza Oktavia Nur (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
The growth of the Sharia economy in Indonesia is evident in the Global Islamic Economy Indicator ranking, however, the Islamic banks have not aligned with these progressive trends. To address this disparity, policymakers should prioritize the development of the Islamic finance industry as a means of stimulating economic growth. Recognizing the vital role of banking as a financial institution, it becomes essential to provide comprehensive support in advancing Islamic banks and facilitating the efficient movement of capital assets within small communities. Therefore, this study aimed to examine the effect of the Bank Indonesia (BI) Rate on the total financing of Islamic Commercial Banks for 2014-2021, with TPF as a moderating variable. Employing a quantitative method, the data approach involved analyzing the classical assumption test descriptively using secondary data from the BUS annual report published on the official website of the bank during the 2014-2015 period. The results showed that the BI Rate did not significantly affect the total financing of Islamic commercial banks. In contrast, third-party funds with the total financing of Islamic commercial banks indicated a significant relationship. The influence of the BI Rate on Islamic commercial bank financing was moderated by third-party funds.